Experimental investigation on the solubility and initial rate of absorption of CO2 in aqueous mixtures of methyldiethanolamine with the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate - Ahmady, A.; Hashim, M.A.; Aroua, Mohamed Kheireddine (American Chemical Society, 2010)
In this paper we present the results of the initial absorption rate and solubility of CO2 in aqueous 4 M methyldiethanolamine (MDEA) mixed with various concentrations of 1-butyl-3-methylimidazolium tetrafluoroborate (bmimBF4) at (303, 313, 323, and 333) K. All experiments were carried out at low partial pressures of CO2, below 110 kPa. The results of this research suggested that the presence of a low concentration of bmimBF4 in aqueous 4 molÂ·L-1 MDEA has no significant effect on the mixture loading capacity, but increased the initial absorption rate. The amine CO2 loading capacity showed a significant decrease in the presence of high concentrations of ionic liquid in the mixture.